WO3 Doped SnS2 Gas Sensor Response to NO2: Effect of Temperature and Humidity Using Transition State Theory Formalism - Abdulsattar, A. (Eurasian Journal of Chemistry, 2025)
Several factors frequently affect gas sensors, including sensing material, doping, temperature, detected gas properties, humidity, manufacturing method, etc. The present work studies WO3 doped SnS2 gas sensor response to NO2, considering the above factors using transition state theory formalism. The reaction rate equation in transition state theory was used to estimate the change in the number of vacancies in a 30 % WO3- doped SnS2 sensor when NO2 gas passed over its surface. Temperature dependence of Gibbs energy of adsorption and transition was evaluated at the effective temperatures. Effective temperatures were the temperatures after which NO2 gas dissociates and can no longer be detected. The effect of temperature and humidity was evaluated using logistic functions. Response, response time, and NO2 concentration were calculated and compared with the experiment. Interestingly, the lowest Gibbs energy of transition as a function of 30 % WO3 doping percentage was very close to the highest experimental response. WO3 doped SnS2 gas sensor is stable for an extended period, as proved experimentally and theoretically. Transition state theory enabled the calculation of changes in the number of vacancies and various experimentally obtained quantities that cannot be evaluated using density functional theory alone.
Keywords: WO3 Doped SnS2; NO2 gas sensor; Density functional theory; Transition state theory; effecting temperature; doping; response time; Gibbs energy